Weed control in cropping sequence based on single and mixed crops - Prasad, K; Quayum, A; Rafey, A (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1991-93 with single-crop sequence of maize (Zea mays L.) wheat (tritiucm aestivum L. emend. Fiori & Paol) and soybean [Glycine max.(L.) Merr.) indian mustard [Brassica juncea (L.) Crernj. & Cosson) and with mixed-crop sequence of maize + soybean-wheat + indian mustard under different weed control methods. The mixed crop sequence proved most effective in reducing population of weeds (36.9 and 29.7%) and dry matter accumulation by weeds (43.8 and 39.1%) and in increasing net profit (128.3 and 29%) compared with single-crop sequence of maize-wheat and soybean-indian mustard respectively. Application of metolachlor @ 0.75 kg/ha pre·emergence in the rainy-season crops and of pendimethalin @ 0.75 kg/ha pre-emergence + isoproturon @ 0.75 kg/ha pre-emergence in the winter-season crops showed 9.4% more control of weeds than the use of fluchloralin @ 1.25 kg/ha pre-plant incorporation in tbe rainy-season crops and isoproturon @ 1.25 kg/ha post-emergence in the winter-season crops in both the years. The treatment was comparable with that of weeding by grubber (15 and 30 days after sowing) in minimizing density and dry weight of weeds and in increasing net profit.